Influence of different phytoremediation on soil microbial diversity and community composition in saline-alkaline land. Issue 5 (16th April 2022) - Li, Fengxia; Guo, Yongzhong; Wang, Zhangjun; Mu, Yangxiu
Abstract: Soil salinization is one main environmental factor restricting plant growth and agricultural productivity. However, phytoremediation is one of the important means to improve saline-alkali soil by planting halophytes or salt-tolerant plants. In order to study whether there are differences among soil microorganisms in different phytoremediation, the effects of four plants, including alfalfa (MX), oil sunflower (YK), maize (YM) and ryegrass (HMC) on soil physicochemical properties, enzyme activity and microbial community diversity and composition were investigated in this study and the relationships between microbial community structure and soil physicochemical properties, enzyme activity were analyzed. The results showed that all plants treatments significantly decreased pH, TS (total saltinity) and BD (bulk density), while increased OM (organic matter), TN (total nitrogen), AN (available nitrogen), TP (total phosphorus), AP (available phosphorus), TK (total potassium) and TPOR (total porosity), and the number of nitrite bacteria reduced by planting at the same time. Except for YM, other treatments significantly increased the number of nitrifying and denitrifying bacteria compared with CK, while only YK increased that of fungi. Additionally, all plants increased the activity of nitrite reductase and decreased that of urease. More interestingly, plants treatments shifted microbial community compositions, and only YM significantly decreased the bacterial diversity and increased the fungal diversity. Redundancy analysis suggested that TK, pH, BD, TS, AN, OM and nitrite reductase, lignin peroxidase were the key environmental factors that shaped the bacterial community structure, while that of fungi was mainly driven by OM, nitrite reductase, urease and lignin peroxidase. The results indicated that MX and YM are the best choice for remediation of saline-alkali soil. These data can provide certain theoretical basis for the further restoration of saline-alkali land. HIGHLIGHTS: The effects of different phytoremediation on microbial diversity and community structure were different. Phytoremediation can significantly decreased pH, TS and BD, while increased OM, TN, AN, TP, AP, TK and TPOR in saline-alkali soil. All plants increased the activity of nitrite reductase and decreased the activity of urease.